Fill in the blanks to follow the steps in solving the equation:

5x−12−6x=−10x+7−1 Step 1: Combine like terms Response area,

Step 2: Get x-terms on same side of equation

Step 3: Get constants on same side of equation

Step 4: Get the x by itself by using the inverse operation

1 answer

Step 1: Combine like terms Response area:
-12 - 1 = -13
-6x - 10x = -16x
-10x + 7 = 7

Step 2: Get x-terms on the same side of the equation:
5x - 16x = -13 - 7x

Step 3: Get constants on the same side of the equation:
-16x - 7x = -13

Step 4: Get the x by itself by using the inverse operation:
-23x = -13

To solve for x, divide both sides of the equation by -23:
x = -13 / -23

The final solution is:
x = 13/23